Beneficial effects of Fu-Zheng-Qu-Zhuo oral liquid combined with standard integrated therapy in patients with chronic kidney disease (stage 3–4): A randomized placebo-controlled clinical trial. Issue 28 (July 2017) - Li, Shen; Rao, Xiang-Rong; Dai, Xi-Wen; Pei, Kun; Wang, Lee; Huo, Bao-Min; Wang, Xiu-Juan; Kong, Ling-Xin; Zhang, Nan-Nan; Lian, Feng-Mei
Abstract: Background: The high worldwide prevalence of chronic kidney disease (CKD) is a critical health problem and the development of more effective therapies is urgently needed. We conducted a randomized, double-blinded, placebo-controlled clinical trial from October 2010 to December 2012 to assess whether Fu-Zheng-Qu-Zhuo oral liquid (FZQZ) has a beneficial effect in preventing CKD progression when added to standard integrated therapies. Methods: Patients with CKD stage 3 to 4 from 3 hospitals in Beijing, China were enrolled. Patients were randomly assigned to the FZQZ or placebo groups and were treated with standard integrated therapy plus FZQZ or placebo (20 mL each time, 3 times/d) for 12 months. Patients received post-trial follow-up until October 2014. The primary outcome was the estimated glomerular filtration rate (eGFR)-Slope (mL/min per 1.73 m2 per month) during the in-trial time, which was calculated by the eGFR regression curve estimated from each serum creatinine measurement during the in-trial period. Secondary outcomes were changes in 24-h urine protein excretion (24-h UP) and albumin and hemoglobin levels from baseline during the in-trial period. Time to composite endpoint events (initiation of long-term dialysis, doubling of serum creatinine, or CKD-related death during the in-trial and post-trial phases) was assessed as a secondary outcome. Results: A total of 68 patients (43 in the FZQZ group and 25 in the placebo group) completed the in-trial and post-trial phases, with an average follow-up time of 31.6 ± 9.6months. The FZQZ group had amean eGFR-Slope of 0.25 ± 1.44 as compared with −0.72 ± 1.46 (mL/min per 1.73m2 per month) in the placebo group during the in-trial period ( P  = .003). The FZQZ group showed decreased 24-h UP, with a change from baseline of −0.08 (interquartile range [IQR], −0.33 to 0.01) versus 0.01 (IQR, −0.19 to 0.33) g/24h in the placebo group ( P  = .049). Decreased risk of composite endpoint events was observed only in the post-trial phase (hazard ratio = 0.42, 95% confidence interval: 0.16–1.11, P  = .038). No significant differences in albumin and hemoglobin level changes were observed. Conclusion: Adding FZQZ oral liquid to standard integrated therapies may aid in attenuating CKD progression. Abstract : Supplemental Digital Content is available in the text